Clinical and histopathological effects of heart failure drug therapy in advanced heart failure patients on chronic mechanical circulatory support. (1st November 2017) - Catino, Anna B.; Ferrin, Peter; Wever‐Pinzon, James; Horne, Benjamin D.; Wever‐Pinzon, Omar; Kfoury, Abdallah G.; McCreath, Lauren; Diakos, Nikolaos A.; McKellar, Stephen; Koliopoulou, Antigone; Bonios, Michael J.; Al‐Sarie, Mohammad; et al.
Abstract : Aims: Adjuvant heart failure (HF) drug therapy in patients undergoing chronic mechanical circulatory support (MCS) is often used in conjunction with a continuous‐flow left ventricular assist device (LVAD), but its potential impact is not well defined. The objective of the present study was to examine the effects of conventional HF drug therapy on myocardial structure and function, peripheral organ function and the incidence of adverse events in the setting of MCS. Methods and results: Patients with chronic HF requiring LVAD support were prospectively enrolled. Paired myocardial tissue samples were obtained prior to LVAD implantation and at transplantation for histopathology. The Meds group comprised patients treated with neurohormonal blocking therapy (concurrent beta‐blocker, angiotensin‐converting enzyme inhibitor/angiotensin receptor blocker, and aldosterone antagonist), and the No Meds group comprised patients on none of these. Both the Meds ( n  = 37) and No Meds ( n  = 44) groups experienced significant improvements in cardiac structure and function over the 6 months following LVAD implantation. The degree of improvement was greater in the Meds group, including after adjustment for baseline differences. There were no differences between the two groups in arrhythmias, end‐organ injury, or neurological events. In patients with high baseline pre‐LVAD myocardial fibrosis, treatment with HF drug therapy was associated with a reduction in fibrosis. Conclusions: Clinical and histopathological evidence showed that adjuvant HF drug therapy was associated with additional favourable effects on the structure and function of the unloaded myocardium that extended beyond the beneficial effects attributed to LVAD‐induced unloading alone. Adjuvant HF drug therapy did not influence the incidence of major post‐LVAD adverse events during the follow‐up period.